Implementasi Psak 69 Agrikultur Tanaman Pisang Cavendish Pada Usaha Dagang Pisang Cavendish Di Jawa Timur - Yusi Putri Eka Vianti; Adi Prasetyo; Dwi Irawan (Akuisisi: Jurnal Akuntansi, 2022)
This study aims to provide an understanding and determine the implementation of Statement of Financial Accounting Standards (PSAK) Number 69 Cavendish Banana Agriculture in the financial statements of Cavendish Banana Trading Business in East Java. The location of this research was carried out at the Cavendish Banana Trading Business in East Java. The type of data used in this research is descriptive qualitative and quantitative data with primary and secondary data sources. The data analysis techniques used were direct observation and interviews, collecting data and examining data, analyzing data and concluding data. The results of the research show that the Cavendish banana trading business in East Java has not yet understood the Statement of Financial Accounting Standards (PSAK) No. 69 of Cavendish Banana Agriculture. , but based on the analysis of the Statement of Financial Accounting Standards (PSAK) No. 69 of Agriculture seen from the recognition that it has been implemented, the measurement has not been implemented, the presentation and disclosure has not been fully implemented. Penelitian ini bertujuan untuk memberikan pemahaman dan mengetahui implementasi Pernyataan Standar Akuntansi Keuangan (PSAK) Nomor 69 Agrikultur Tanaman Pisang Cavendish pada laporan keuangan Usaha Dagang pisang cavendish di Jawa Timur. Lokasi peelitian ini dilakukan pada Usaha Dagang pisang cavendish di Jawa Timur. Jenis data yang digunakan dalam penelitian ini adalah jenis data deskriptif kualitatif dan kuantitatif dengan sumber data primer dan sekunder. Teknik analisis data yang digunakan adalah observasi dan wawancara secara langsung, pengumpulkan data dan memeriksa data, menganalisis data dan menyimpulkan data. Hasil peneitian menunjukkan bahwa Usaha Dagang pisang cavendish di Jawa Timur belum memahami Pernyataan Standar Akuntansi Keuangan (PSAK) Nomor 69 Agrikultur Tanaman Pisang Cavendish, Usaha Dagang pisang cavendish di Jawa Timur belum menerapkan Pernyataan Standar Akuntansi Keuangan (PSAK) Nomor 69 Agrikultur dalam pencatatan laporan keuangannya, tetapi berdasarkan analisis dari Pernyataan Standar Akuntansi Keuangan (PSAK) Nomor 69 Agrikultur dilihat dari pengakuan sudah menerapkan, pengukuran belum menerapkan, penyajian dan pengungkapan belum sepenuhnya menerapkan.